Britain, Empire and the Origins of the Cold War Youth Race. Issue 2 (2nd April 2016) - Sutton, Christopher
Abstract: The Soviet politicization of international youth during the inter-war and wartime years was identified by British policy-makers as a most serious threat to British imperial power. Asserting the significance of and interplay between colonial youth and imperial ideology in the politics of the cultural Cold War, this article thus examines how the British conceptualized and sought to compete in the Cold War 'youth race' between 1945 and 1949. While funding was the most obvious disadvantage, this article argues that Britain's fatal weakness was its inability to escape the consequences of colonialism, including the tendency to rely on repressive legislation.